Organizational animosity and its impact on the occurrence of organizational deviance: an exploratory study of the views of a sample of employees in many of government directorates in zakho city - Tawfiq, Hindav; Khaled Amedi, Green (Humanities Journal of University of Zakho, 2023)
The current study aims to present the concept of organizational animosity as one of the most important contemporary problems and its impact on the occurrence of organizational deviance as a dilemma under which all negative, destructive behaviors that would harm organizations fall. The research was been carried out at many governmental organizations in the city of Zakho, totaling 18 governmental organizations. to achieve the desired results of the study, it relied on what was available in the subject literature that dealt with the study variables to build the theoretical and methodological frameworks for it. As the study directed, through its general framework, to define the stud’s problem by asking number questions that revolve around the nature of the correlation and regression relationship between the independent variable represented by organizational anemia and the dependent variable represented by organizational deviance. A questionnaire was been designed to collect field-framework data, and the research sample consisted of (250) workers in those governmental organizations investigated in the city of Zakho. While the statistical analysis of the data was been carried out using the statistical software (SPSS) and many statistical indicators were been calculated, which formed the basis for the presentation and discussion of the results of the field analysis. The study came up with a set of conclusions, the most important of which is the existence of a positive, there is a significant correlation between organizational hostility and organizational deviance, and that organizational sedation as an independent variable affects organizational deviance as a dependent variable. A set of proposals were been developed that focused on the need for the administrative leaders in governmental organizations to see the practical reality experienced by their working members and try to contact them and know the problems they suffer from by meeting and discussing with them the obstacles they suffer from within their organizations and trying to find ways that it have been hoping to benefit Including the relevant government organizations in the city of Zakho to get rid of the destructive behaviors of organizational deviance and suggesting some titles for future studies that will help the organizational field.